Israel Journal of Plant Sciences - Israel Journal of Plant Sciences (Brill, 2026)
The Israel Journal of Plant Sciences is an international journal of extensive scope that publishes special issues dealing with all aspects of plant sciences, including but not limited to: physiology, cell biology, development, botany, genetics, ecology, evolution, ecophysiology, plant-microbe interaction, agronomy, and soil-plant-atmosphere continuum.
FI 0.21
Q4
Keywords: Botany & plant sciences; Botánica; Acuerdos transformativos; Transformative agreements; Ciencias vegetales; Biología celular; Ecología